The effects of the number of links and navigation support on cognitive load and learning with hypertext: The mediating role of reading order. - Madrid-López, Rafael Ignacio; Van Oostendorp, Herre; Puerta-Melguizo, Mari Carmen (Elsevier, 2009)
Problems in learning with hypertext systems have been claimed to be caused by high levels of disorientation and cognitive load. This was recognized by DeStefano and LeFevre [DeStefano, D., & LeFevre, J. -A., (2007). Cognitive load in hypertext reading: A review. Computers in Human Behavior, 23(3), 1616–1641.] who predicted an increase of cognitive load and impairment of learning for hypertexts with a higher number of links per page. From a practical perspective, several navigation support techniques, such as providing link suggestions, have been proposed for guiding learners and reducing cognitive overload. In an experiment, we tested DeStefano and LeFevre’s predictions as well as the usefulness of link suggestions. Participants used different versions of a hypertext, either with 3-links or 8-links per page, presenting link suggestions or not. We tested their cognitive load and learning outcomes. Results showed that there was a benefit of using link suggestions for learning, but no effect of number of links on learning was found. Moreover, the effects of our manipulations on cognitive load were mediated by the reading order that participants selected. Implications for research and the design of navigation support systems are discussed.
Política de acceso abierto tomada de: https://www.sherpa.ac.uk/id/publication/12514
Keywords: Hipertexto; Interfaces de usuario; Interacción hombre-ordenador; Hypertext comprehension; Cognitive load; Navigation support